2014
DOI: 10.1074/jbc.m114.557009
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-5a Ligand Modulates Mitochondrial Fission-Fusion in Rat Hippocampal Neurons

Abstract: Background: Mitochondrial dynamics play a role in maintaining energy production and metabolism in mammalian cells. Results: Wnt-5a signaling stimulated mitochondrial dynamics in neurons, triggering the fission-fusion process through calcium mobilization. Conclusion: Wnt-5a signaling controls mitochondrial morphology and dynamics in postsynaptic regions. Significance: Noncanonical Wnt-5a signaling modulates mitochondrial dynamics in normal neurons, and it is a new therapeutic target for brain disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 68 publications
0
58
0
Order By: Relevance
“…The Wnt pathway plays an essential role during the development, and Wnt components participate as key players in the development of the central nervous system (61). Previous evidence suggests that Wnt proteins act as a potent modulator of mitochondrial dynamics and initiate the process of mitochondrial fission and fusion in the hippocampal neurons of rodents (59,60). Therefore, increased mitochondrial fission by BPA observed in the present study could also be due to impaired expression and levels of Wnt proteins.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The Wnt pathway plays an essential role during the development, and Wnt components participate as key players in the development of the central nervous system (61). Previous evidence suggests that Wnt proteins act as a potent modulator of mitochondrial dynamics and initiate the process of mitochondrial fission and fusion in the hippocampal neurons of rodents (59,60). Therefore, increased mitochondrial fission by BPA observed in the present study could also be due to impaired expression and levels of Wnt proteins.…”
Section: Discussionmentioning
confidence: 44%
“…Inhibition of excessive mitochondrial fission reduces aberrant autophagy and prevents neurodegeneration (58). The observed alterations in mitochondrial dynamics by BPA in the present study could also be explained on the basis of alterations in the Wnt/␤-catenin pathway (59,60). In our earlier studies we found that BPA exposure down-regulated the expression and levels of Wnt proteins (2).…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, pyruvate can translocate into the mitochondria due to the production of ATP. We observed that treatment with the Wnt3a ligand increased the levels of the major substrate for ATP synthesis, ADP, thereby suggesting that this pathway activates the oxidative metabolism of glucose in neurons (37,63). Meanwhile, we did not observe changes in the regulatory enzyme G6PDH and in the overall PPP.…”
Section: Wnt Signaling Stimulates Glucose Utilization In Neuronsmentioning
confidence: 56%
“…The activity of the Wnt signaling pathway is essential for the development and function of central synapses that modulate several process, such as adult hippocampal neurogenesis, the establishment of synapses, neuronal firing activity, neuronal plasticity, nerve transmission, dendritic spine formation, and mitochondrial dynamics (2,(35)(36)(37)(38)(39). The deregulation of Wnt activity by loss or gain of function has been associated with the progression of various diseases, including cancer, diabetes mellitus type II, fibrosis, and AD (6,30,40,41).…”
Section: Wnt Signaling Stimulates Glucose Utilization In Neuronsmentioning
confidence: 99%
“…The mitochondrial network was 3-dimensionally reconstructed as previously described [39] from mito-Cherry-transfected neurons. To overexpress mito-Cherry, we used NeuroMag (OZ Bioscience, Marseille, France) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%